Pengabdian Masyarakat Penggunaan Antibiotik yang Bijak pada Ibu Rumah Tangga di Desa Punggul Kabupaten Badung - Widowati, I Gusti Ayu Rai; Maharianingsih, Ni Made; Maharjana, Ida Bagus Nyoman; Sutema, Ida Ayu Manik Partha (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Background: Antimicrobial resistance (AMR) is an increasing global health challenge, especially due to the irrational use of antibiotics. Increasing public awareness of the dangers of AMR is an important step in prevention and control efforts. A counseling program on AMR awareness has been implemented as part of the Community Service Program by Bali International University students in Punggul Village, Badung Regency, Bali Province. Method: This community service activity was carried out on September 5, 2023 and was attended by more than 50 participants, the majority of whom were housewives. The methods used included the presentation of educational materials, interactive sessions, and local culture-based campaigns to increase public understanding regarding the proper and wise use of antibiotics. Results: Evaluation through posttest showed that there was fair knowledge (73.0%) and positif attitude of participants (100%) regarding the importance of rational use of antibiotics. In addition, this activity had a positive impact on students as implementers, especially in improving communication skills, leadership, and community empowerment. Conclusion: This program showed that a community-based educational approach that is sensitive to the local context has significant potential in raising awareness of AMR. Active involvement of young people as agents of change can be a sustainable strategy to support AMR control efforts at the local and global levels.